Enhancing Student Academic Performance through Engagement and Learning Resources in Project Self - Villaruel, Jordan V (Researchparks Publishing, 2025)
The research examines the functionality of Project SELF (Strengthening Engagement and Learning Foundations) in enhancing the academic performance of Senior High School students at Southville 1 Integrated National High School, specifically in the subject Introduction to the Philosophy of the Human Person. Recent studies have shown that contextualized learners’ activity sheets significantly improve students’ academic performance. The research addresses students’ low Mean Percentage Score (MPS) in the subject by utilizing structured activity sheets to enhance student engagement, critical thinking, and foundational learning skills. Moreover, few studies have examined activity sheets in Introduction to the Philosophy of the Human Person as supplementary materials. Their effectiveness is well-documented in other subjects, and their potential to enhance understanding and critical thinking in this subject is still unexplored. An experimental research design with pre-test and post-test methods was employed to measure the impact of Project SELF. The results indicate a significant improvement in students’ post-test scores, demonstrating the activity sheets’ effectiveness in enhancing learning outcomes. The study concludes structured activity sheets can be a valuable supplementary learning resource in Introduction to the Philosophy of the Human Person. Recommendations to strengthen student academic performance further include continuously enhancing Project SELF materials, integrating more active learning strategies, and encouraging collaborative learning among students. Additionally, the study suggests institutionalizing Project SELF to ensure its sustainability by incorporating it into the school’s learning framework, reviewing and revising the contents of the activity sheets based on the lowest-scoring items and providing instructional coaching for teachers on Project SELF integration.